Outcome of Isolated Absent Septum Pellucidum Diagnosed by Fetal Magnetic Resonance Imaging (MRI) Scan. (October 2018) - Vawter-Lee, Marissa M.; Wasserman, Halley; Thomas, Cameron W.; Nichols, Beatrice; Nagaraj, Usha D.; Schapiro, Mark; Venkatesan, Charu
Improved fetal imaging has resulted in increased diagnosis of isolated absent septum pellucidum without other intracranial abnormalities. There is little literature regarding outcomes for these fetuses. This study hypothesized the majority of infants diagnosed by fetal magnetic resonance imaging (MRI) with isolated absent septum pellucidum would retain this diagnosis postnatally. Specifically, in the absence of postnatal endocrine or ophthalmologic abnormalities, postnatal imaging would find no additional related findings, and fetuses would be at low risk for developmental delay. Two of 8 subjects met postnatal criteria for septo-optic dysplasia; remaining subjects had normal postnatal endocrine and ophthalmologic evaluations and no significant related findings on postnatal MRI. One subject without septo-optic dysplasia had delays on developmental screening; all others had normal screening (range of follow-up 8-72 months). Our study questions the necessity of postnatal imaging for prenatally diagnosed isolated absent septum pellucidum. Majority of fetuses with isolated absent septum pellucidum retained this diagnosis postnatally.